Spectral sensitivity of guppy visual pigments reconstituted in vitro to resolve association of opsins with cone cell types. (October 2016) - Kawamura, Shoji; Kasagi, Satoshi; Kasai, Daisuke; Tezuka, Ayumi; Shoji, Ayako; Takahashi, Akiyoshi; Imai, Hiroo; Kawata, Masakado
Highlights: Visual pigments of the guppy ( Poecilia reticulata ) were reconstituted in vitro . Two LWS-1 alleles explain the "yellow" cone classes of Trinidad and Cumana guppies. The guppy LWS-3 is ∼40-nm short-wave shifted from the "five-sites" prediction. Co-expression of LWS-1 and LWS-3 in the guppy "green-yellow" cones is suggested. Relative expression level of LWS s may differ substantially among guppy individuals. Abstract: The guppy ( Poecilia reticulata ) shows remarkable variation of photoreceptor cells in the retina, especially those sensitive to middle-to-long wavelengths of light. Microspectrophotometry (MSP) has revealed varying "green", "green-yellow" and "yellow" cone cells among guppies in Trinidad and Venezuela (Cumana). In the guppy genome, there are four "long-wave" opsin loci ( LWS-1, - 2, - 3 and - 4 ). Two LWS-1 alleles have potentially differing spectral sensitivity ( LWS-1 /180Ser and LWS-1 /180Ala ). In addition, two "middle-wave" loci ( RH2-1 and - 2 ), two "short-wave" loci ( SWS2-A and - B ), and a single "ultraviolet" locus ( SWS1 ) as well as a single "rhodopsin" locus ( RH1 ) are present. However, the absorption spectra of these photopigments have not been measured directly and the association of cell types with these opsins remains speculative. In the present study, we reconstituted these opsin photopigments in vitro . The wavelengths of maximal absorbance (λmax ) were 571 nm ( LWS-1 /180Ser ), 562 nm ( LWS-1 /180Ala ), 519 nm ( LWS-3 ), 516 nm ( LWS-2 ), 516 nm ( RH2-1 ), 476 nm ( RH2-2 ), 438 nm ( SWS2-A ), 408 nm ( SWS2-B ), 353 nm ( SWS1 ) and 503 nm ( RH1 ). The λmax of LWS-3 is much shorter than the value expected (560 nm) from the "five-sites" rule. The two LWS-1 alleles could explain difference of the reported MSP λmax values for the yellow cone class between Trinidad and Cumana guppies. Absence of the short-wave-shifted LWS-3 and the green-yellow cone in the green swordtail supports the hypothesis that this cell class of the guppy co-expresses the LWS-1 and LWS-3 . These results reveal the basis of variability in the guppy visual system and provide insight into the behavior and ecology of these tropical fishes.